2021
DOI: 10.3390/medsci9020037
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serum Circulation of Cell-Free DNA Following Chemotherapy in Breast Cancer Patients

Abstract: Breast cancer is the most common malignancy in women, with alarming mortalities. Neoadjuvant treatments employ chemotherapy to shrink tumours to a well-defined size for a better surgical outcome. The current means of assessing effectiveness of chemotherapy management are imprecise. We previously showed that breast cancer patients have higher serum circulating cell-free DNA concentrations. cfDNA is degraded cellular DNA fragments released into the bloodstream. We further report on the utility of cfDNA in assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…DNA integrity was lower in healthy individuals, probably due to low necrotic activity in body tissues, thereby lowering the concentration of longer DNA fragments in the blood stream. 15 In this study, we found that patients with benign lesions, early and advanced stages of breast cancer had statistically significant higher ALU-115, and ALU-247 levels and DNA integrity in comparison to the control group, (p=0.018, p<0.001 and p=0.019, respectively). These results are consistent with the data obtained from a study by Hussein et al, 2019, indicated that ALU-247, ALU-115 expression, and cf-DNA integrity concentration showed a trend to increase with breast cancer stage, where the mean values of these parameters were significantly higher in breast cancer patients with stages II, III, and IV than healthy subjects (p=0.001, p=0.002 and p=0.009, respectively).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…DNA integrity was lower in healthy individuals, probably due to low necrotic activity in body tissues, thereby lowering the concentration of longer DNA fragments in the blood stream. 15 In this study, we found that patients with benign lesions, early and advanced stages of breast cancer had statistically significant higher ALU-115, and ALU-247 levels and DNA integrity in comparison to the control group, (p=0.018, p<0.001 and p=0.019, respectively). These results are consistent with the data obtained from a study by Hussein et al, 2019, indicated that ALU-247, ALU-115 expression, and cf-DNA integrity concentration showed a trend to increase with breast cancer stage, where the mean values of these parameters were significantly higher in breast cancer patients with stages II, III, and IV than healthy subjects (p=0.001, p=0.002 and p=0.009, respectively).…”
Section: Discussionmentioning
confidence: 52%
“…Also elevated rates of cf-DNA in the blood of cancer patients may be caused by elevated rates of cellular proliferation in tandem with elevated rates of various forms of cell death, which are characteristic biological features of tumor growth. 13 Multiple studies also have indicated elevated levels of cf-DNA in breast cancer, [14][15][16] and several other malignancies as colorectal cancer, lung cancer, testicular cancer, prostate cancer, ovarian cancer and other solid tumors. 10 Many gene sequences such as the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene, ß-globin-gene, human telomerase reverse transcriptase (hTERT), LINE1 (long interspersed nucleotide elements) were studied as biomarkers in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al observed an increasing trend associated with tumor shrinkage (p < 0.05) in the course of NACT and a higher cfDI in eBC patients exposed to NACT who achieved pCR at surgery [125]. Conversely, two other studies showed a progressive clearance of cfDNA and cfDI in the course of NACT [126,127]. A downtrend of short and longer ALU amplicons from cycle one to six of NACT was observed in pCR patients, whereas an increase was observed in non-responders (p = 0.033) [127].…”
Section: Fragmentomicsmentioning
confidence: 97%
“…The size distribution of cfDNA and the cfDI variations have been described also under adjuvant/neoadjuvant treatment [33][34][35]. Wang et al observed that the cfDI increased after neoadjuvant treatment in twenty-nine locally advanced BC patients as a consequence of the tumor shrinkage; in particular, patients undergoing complete pathological response presented a higher cfDI than patients with distant disease-progression after surgery [33].…”
Section: Size Of Cfdna Fragments and Cfdna Integritymentioning
confidence: 99%